Frasa Bahasa Mairasi: Phrases in Mairasi Language - Antonius Maturbongs (Balai Bahasa Provinsi Papua, 2021)
Phrase only filling one function in clause. To strengthen clarification above cited one congeniality [of] phrase supporting [it] made by Elson Pickket and (1976: 73), namely